SYMBOLIC POWER AND EMPLOYEE SILENCE IN HIGHER EDUCATION: NAVIGATING MALAY RIAU CULTURAL VALUES FOR ORGANIZATIONAL TRANSFORMATION - Muhammad Gaza Wiriadi; Riani Rachmawati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study explores the dynamics of power relations and employee silence within a higher education institution in Riau, Indonesia, deeply rooted in Malay cultural values. While modern organizations aim for sustainable transformation through meritocracy, local cultural values such as